Metas académicas y factores motivacionales: Área inglés en alumnos de 4° años de una institución educativa pública - Callao - Solis Esteban, Diana Miriam (2011)
The purpose of this research was to relate the Academic goals and Motivational components’ variables in the area of English. One hundred forty-nine fourth-grade public high-school students from Callao participated in the sample. Their ages varied from fourteen to nineteen years old. The questionnaire about Academic goals from Núñez, Gonzáles-Pienda, Gonzáles-Pumariega, García and Roces (1977), adapted by Solís (2010), and the Motivational components in the area of English by Alarcón (2005), adapted by Solís (2010), were used during this evaluation. The result of the research revealed a low and negative correlation between both variables. Moreover, the psychometric data from the adaption of both questionaires displayed valid and reliable tests.